Health-related hardiness and the effect of a psycho-educational group on clients' symptoms - Austin, W.; Pollard, Cheryl (My University, 1999)
In the health literature, an individual's ability to resist illness when under stress has been referred to as ‘hardiness’. Resources, which may be used to sustain a sense of well being, can be categorized by two broad domains, ‘control’ and ‘commitment and challenge'. In this research, a quasi-experimental nonequivalent control group design was used to determine the impact of a specific clinical nursing intervention (the Wellness Program) in terms of its usefulness in fostering the development of health-related hardiness. Findings demonstrated a significant reduction in symptoms related to obsessive compulsiveness, hostility, psychoticism and average level of distress after subjects completed a relatively short psycho-educational health promotion group. Subjectively, the treatment group subjects also described positive changes in thoughts, feelings and behaviours. This research has implications for clinical interventions using small groups to promote health.
Keywords: health promotion; health-related hardiness; mind-body interrelationship; psycho-educational group; stress